Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.12968/bjsn.2011.6.6.294
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of school-based youth health nursing

Abstract: The aim of this research is to explore the meaning of the experience of school-based youth health nursing in Queensland, Australia. The research follows a qualitative approach and is based on in-depth interviews. The dominant experience is negative because participants feel they have to battle to gain respect and survive in the school environment. The small, positive experience of school-based youth health nursing is related to student consultations. Student consultations are a ‘golden egg’ because participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…SBYHN have not adopted contemporary health promotion practices or addressed health promotion policy reform and collaborative partnerships in schools. SBYHN have not advanced the fundamental concepts of health promotion and have not moved toward green health promotion . This leads us to ask: What can be done to foster collaborative partnerships between health and education for green health promotion in schools ?…”
Section: Implications For School Healthmentioning
confidence: 99%
“…SBYHN have not adopted contemporary health promotion practices or addressed health promotion policy reform and collaborative partnerships in schools. SBYHN have not advanced the fundamental concepts of health promotion and have not moved toward green health promotion . This leads us to ask: What can be done to foster collaborative partnerships between health and education for green health promotion in schools ?…”
Section: Implications For School Healthmentioning
confidence: 99%
“…One participant holds a qualifi cation in health promotion. Further details about the participants' qualifications and experience can be found in Sendall (2009) and Sendall, Fleming, and Lidstone (2011).…”
Section: The Manual For Child and Youth Healthmentioning
confidence: 99%
“…Poor understanding of the school nurse's role (Newell et al, 2003;Rice et al, 2005;Merrel et al, 2007;Buckley et al, 2009;Smith & Firmin, 2009), and a lack of understanding of professional responsibilities and legal requirements of nursing professionals (Newell et al, 2003;Rice et al, 2005;Broussard, 2007;Smith & Firmin, 2009;Sendall et al, 2011), are the most commonly identified challenges discussed in school nursing literature internationally.…”
Section: Key Challenges Of the School Nursing Rolementioning
confidence: 99%
“…Role strain has frequently been attributed to a lack of understanding of school nurses' legal and professional responsibilities by school authorities and parents (Barnes et al, 2004a;Buckley et al, 2009;Sendall, 2009;Smith & Firmin, 2009). The perception of a lack of role clarity persists primarily due to a fundamental misunderstanding of the meaning of the concepts used to describe the role, rather than a failure to clearly define the role.…”
Section: Role Expectationsmentioning
confidence: 99%
See 1 more Smart Citation